Antihyperlipidemic Effect of Bitter Melon Extract (Momordica Charantia L.) in Wistar Rats - Evi Sovia; Rini Roslaeni; Sutan Bagas Prakasa; Amallia Ardila Putri; Akmal Dhaffa Ulhaq; Daswara Djajasasmita; Khomaini Hasan; Welly Ratwita (Universitas Padjadjaran, 2022)
The use of alternative medicine, especially medicinal plants to treat various diseases including hyperlipidemia has increased over the last few decades in most countries around the world. Bitter melon (Momordica charantia) contains active ingredients such as flavonoids, tannins, saponins and polyphenols which have antihyperlipidemic effects. The study aims to determine the antihyperlipidemic effect of bitter melon aqueous extract and compare it with simvastatin in reducing total cholesterol and low- density lipoprotein (LDL), and increasing high-density lipoprotein (HDL) in male Wistar strain rats. The research is an experimental study with pre and post-test design, carried out in October-December 2021 at the Faculty of Medicine, Universitas Jenderal Achmad Yani, Cimahi Indonesia. Subjects consisted of 25 Wistar rats which were divided into five groups. The negative control group (standard diet), the positive control group (induced by a high-fat diet and propylthiouracil), and the three groups that were induced by a high-fat diet and propylthiouracil then given bitter melon extracts of 300 and 600 mg/ kg BW and simvastatin 10 mg/kg BW. The method of measuring cholesterol using the Cholesterol Oxidase-Perioxidase Aminoantipyrine (CHOD-PAP) enzymatic method principle with a Semi-automatic Chemistry Analyzer. Analysis using paired t-test. The results showed a significant difference (P<0.005) in HDL and total cholesterol levels in the 600 mg/kg BW dose group, and a significant difference in LDL level in the 300 mg/kg BW dose group. The Simvastatin group showed significant differences in HDL, LDL, and total cholesterol. This is presumably because the active substances in bitter melon can inhibit the HMG-CoA reductase enzyme so that it can reduce LDL and total cholesterol levels. It can be concluded that bitter melon aqueous extract at doses 300 and 600 mg/Kg BW can reduce total and LDL cholesterol levels, and increase HDL. Keywords: antihyperlipidemic, HDL, LDL, Momordica charantia, total cholesterol Efek Antihiperlipidemik Ekstrak Buah Pare (Momordica Charantia L.) pada tikus WistarAbstract Penggunaan pengobatan alternatif, terutama tanaman obat untuk mengobati berbagai penyakit termasuk hiperlipidemia telah meningkat selama beberapa dekade terakhir di sebagian besar negara di seluruh dunia. Pare (Momordica charantia L.) mengandung bahan aktif flavonoid, tanin, saponin dan polifenol yang memiliki efek antihiperlipidemia. Tujuan penelitian untuk mengetahui efek antihiperlipidemia ekstrak air buah pare dan membandingkannya dengan simvastatin dalam menurunkan kolesterol total dan low density lipoprotein (LDL), serta meningkatkan high density lipoprotein (HDL) pada tikus jantan galur Wistar. Penelitian ini merupakan penelitian eksperimental dengan desain pre and posttest, dilaksanakan bulan Oktober-Desember 2021 di Fakultas Kedokteran Universitas Jenderal Achmad Yani Cimahi Indonesia. Subjek penelitian adalah 25 ekor tikus Wistar yang dibagi menjadi lima kelompok. Kelompok kontrol negatif (diet standar), kelompok kontrol positif (diinduksi diet tinggi lemak dan propiltiourasil), dan tiga kelompok yang diinduksi diet tinggi lemak dan propiltiourasil kemudian diberikan ekstrak pare 300 dan 600 mg/kgbb dan simvastatin 10 mg/kgbb. Analisis menggunakan uji t berpasangan. Hasil penelitian menunjukkan perbedaan bermakna (P<0,005) kadar HDL dan kadar kolesterol total pada kelompok dosis 600 mg/kgbb, dan perbedaan kadar LDL bermakna pada kelompok dosis 300 mg/kgbb. Kelompok simvastatin menunjukkan perbedaan bermakna untuk HDL, LDL, dan kolesterol total. Hal ini diduga karena buah pare mengandung zat aktif yang dapat menghambat enzim HMG-CoA reduktase sehingga dapat menurunkan kadar LDL dan kolesterol total. Dapat disimpulkan bahwa ekstrak air buah pare dengan dosis 300 dan 600 mg/kgbb dapat menurunkan kadar kolesterol total dan LDL, serta meningkatkan HDL.Kata kunci: antihiperlipidemi, HDL, LDL, kolesterol total, Momordica charantia